The potential impact of internet transactions on monetary policy, with special reference to small open economies of the Caribbean - Henry, Lester ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 2000)
Examines the potential impact of e-money on the relative ability of central banks to conduct monetary policy.